Economic barriers and gaps to reach the desirable consumption of salt, sugar, and fat in Iran: a qualitative study - Mohammad Amerzadeh; Amirhossein Takian; Hamed Pouraram; Ali Akbari Sari; Afshin Ostovar (BMC, 2023)
Abstract Background Non-communicable diseases (NCDs), also known as chronic diseases, specifically cardiovascular diseases (CVD), cancers, respiratory diseases, and diabetes are the main reason for more than two-thirds of global deaths, in which the unhealthy diet is one of the primary risk factors. The golden solution to reducing obesity and CVD linked to an unhealthy diet is to reduce calories, salt, sugar, and fat intake. Besides, activities highlighting lifestyles that contain healthy diets usually focus on reducing salt, sugar, and saturated fat consumption. As a result, the researchers aimed to study the gaps and economic barriers to recommended consumption of salt, sugar, and fat in Iran, based on WHO recommendations. Methods This is a qualitative study. We conducted semi-structured and in-depth interviews with 30 stakeholders, including academics, experts, and key informants in different sectors from December 2018 until August 2019 in Tehran, Iran. We used a purposeful and snowball sampling method to select participants. All interviews were transcribed verbatim and thematically analyzed using MAXQDA 11. Results Economic problems and inflation in Iran caused people to eat more unhealthy foods, while a healthy diet consumption was reduced due to higher prices. Unfair political sanctions imposed on the country caused economic pressure and adversely affected family nutrition. Worse still, despite legal bans, advertising unhealthy foods via media, mainly to generate revenue, encouraged more consumption of unhealthy food. The lack of targeted subsidies and failure in tax legislation and implementation related to the unhealthy products deteriorated the conditions. Conclusion Some economic barriers have hampered plans to reduce salt, fat, and sugar consumption in Iran. Fundamental reforms in the tax and subsidy system are required to improve people's eating habits. In particular, citizens' income that has been continuously shrinking due to economic conditions, imposed sanctions, and the inevitably high inflation needs to be addressed urgently. Unless the government of Iran deals with the economic barriers to healthy nutrition, the pathway for implementing the national action plan for prevention and control of NCDs toward a 30% mortality reduction due to NCDs by 2030 looks unlikely to reach.